Anti-Inflammatory Activity of Two Labdane Enantiomers from Gymnosperma glutinosum: An In Vivo, In Vitro, and In Silico Study - Salud Pérez-Gutiérrez; Nimsi Campos-Xolalpa; Sofía A. Estrada-Barajas; Alan Carrasco-Carballo; Angel Mendoza; Ernesto Sánchez-Mendoza (Pharmaceuticals)
Background/Objectives: Diseases associated with inflammatory processes continue to grow steadily throughout the world. Unfortunately, prolonged use of drugs induces adverse effects ranging from hypersensitivity reactions to damage to the digestive system. These negative effects open the possibility of continuing the search for anti-inflammatory compounds with less toxicity. The aim of this research was to isolate and evaluate the anti-inflammatory activity of a mixture of two enantiomeric labdanes isolated from Gymnosperma glutinosum by in vivo, in vitro, and in silico methods. Methods: A brief description of the main methods or treatments applied. This can include any relevant preregistration or specimen information. The structure of the labdanes enantiomers was elucidated by X-ray crystallography and spectroscopies methods. The anti-inflammatory effect was evaluated on a mouse model of ear edema induced with 12-O-tetradecanoyl phorbol-13-acetate; the pro-inflammatory mediators, nitric oxide (NO) and interleukin (IL-6), were quantified on macrophages stimulated with lipopolysaccharide, and the interaction between labdanes and diana was studied by molecular docking. Results: We identified the chemical structures of two new labdane enantiomers: a-gymglu acid and b-ent-gymglu acid. The enantiomer mixture, named gymglu acid, diminished ear edema at doses of 1 and 2 mg/ear by 36.07% and 41.99%, respectively. A concentration of 155.16 µM of gymglu acid inhibited the production of NO by 78.06% and IL-6 by 71.04%. The in silico results suggest two routes by which these labdanes reduce inflammation: partial agonism toward the corticosteroid receptors and inhibition of nitric oxide synthases. Conclusions: These results show that the gymglu acid enantiomers have promising anti-inflammatory activity.